Pathological anatomy and physiology of vascular disease in the lower limbs: submitted for the Gunning Victoria Jubilee Prize in Pathology - Wilson, Graham Malcolm (The University of Edinburgh, 1949)
During recent years the Literature on peripheral vascular disease has grown enormously. Especially frequent have been articles on the clinical features and the response to treatment, but strangely enough since the publication of Buerger's book (1924) relatively little has been written on the correlation of the morbid anatomical appearances and the physiological readjustment of the circulation. This is all the more surprising in view of the fact that so much attention. has been directed to functional derangement of the arterial circulation in the heart and kidney, especially as it is so much simpler to Make absolute measurements of the arterial circulation in the limb than in the other organs.

The present study is based on material obtained from a variety of sources my interest was first aroused in the subject by experience gained in the investigation of material kindly supplied by prof. J. R. Learmonth from his peripheral vascular diseases unit. .part from one biopsy performed on a superficial vein this material consisted of lower limbs amputated as a result primarily of ischaemic gangrene. The greater part of this work accordingly consists of an account of observations made in examining This tissue in the Pathology Department of the University of Edinburgh. The study has however been continued in the Medical Unit of St. Mary`s Hospital in an attempt to answer some of the questions raised during the course of the investigations made Edinburgh)and a brief account of some of this later work will accordingly be included.

Although many specimens were available in the departmental collections of the R.I.'S. and the university of Edinburgh pathology Department the account has been restricted to include only cases of thromboangiitis obliterans and atherosclerosis personally studied. Thus every case on which this account is based has been investigated by me both in the ward ana in the laboratory. This is considered to be a most valuable point, namely that both the anatomical and physiological aspects should be studied by one and the same person.